PENGARUH PENYULUHAN TENTANG ASI EKSKLUSIF TERHADAP PENGETAHUAN IBU HAMIL PRIMIGRAVIDA YANG MENIKAH DINI DI WILAYAH KERJA PUSKESMAS PELANGAN - Ismiati; Siti Maryam (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Abstract: WHO (World Health Organization) and UNICEF (United Nations Children's Fund) recommend that babies not be fed anything other than breast milk for the first 6 months. Objective: To determine the effect of education about exclusive breastfeeding on the knowledge of primigravida pregnant women who marry early. Method: This research is a type of quantitative research with a quasi-experimental design. The sample in this study was 15 primigravida pregnant women who married early in the Pelangan Community Health Center Work Area in 2023 using total sampling technique. Data collection tools use pre-test and post-test questionnaires. Data analysis used the Paried t-test. Results: Of the 15 respondents, the average knowledge before the counseling was carried out (Pretest), the mean knowledge value was 69.13 and after the counseling the mean value was 86.73. Furthermore, the results of the research data analysis using the paried t-test showed that there was an influence of education about exclusive breastfeeding on the knowledge of Primigravida pregnant women who married early (p value=0.000<a0.05). Conclusion: There is a significant influence between counseling about exclusive breastfeeding on the knowledge of primigravida pregnant women who marry early in the Pelangan Community Health Center Work Area in 2023.